Information Design in Insurance Markets: Selling Peaches in a Market for Lemons - Daniel Garcia; Roee Teper; Matan Tsur (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper characterizes the optimal information structure in competitive insurance markets with adverse selection. A regulator assigns ratings to individuals according to their risk characteristics, insurers offer fixed insurance contracts to each rating group, and the market clears as in Akerlof (1970). The optimal rating system minimizes ex-ante risk subject to participation constraints. We prove that in any such market there exists a unique optimal system under which all individuals trade and the ratings match low risk types with high risk types negative assortatively. A simple algorithm yields the optimal system. We examine implications for government regulations of insurance markets.
Keywords: D82; 330; insurance markets; adverse selection; information design